Bernard Berenson : a life in the picture trade - Cohen, Rachel (Jewish lives, 2013)
"Few would have predicted that Bernard Berenson, from a poor Lithuanian Jewish immigrant family, would rise above poverty. Yet Berenson left his crowded home near Boston's railyards and transformed himself into the world's most renowned expert on Italian Renaissance paintings, the owner of a beautiful villa and an immense private library in the hills outside Florence. The explosion of the Gilded Age art market and Berenson's work for dealer Joseph Duveen supported a luxurious life, but it came with painful costs: Berenson hid his origins and, though his attributions remain foundational, felt that he had betrayed his gifts as a critic and interpreter of paintings. This finely drawn portrait of Berenson, the first biography devoted to him in a quarter century, draws on new archival materials that bring out the significance of his secret business dealings and the central importance of several women in his life and work: his sister Senda Berenson; his wife Mary Berenson; his patron Isabella Stewart Gardner; his lover Belle da Costa Greene; his dear friend Edith Wharton, and the companion of his last forty years, Nicky Mariano. Rachel Cohen explores Berenson's inner world and extraordinary visual capacity while also illuminating the historical forces-new capital, the developing art market, persistent anti-Semitism, and the two world wars-that profoundly affected his life"--